Radiographic cervical spine injury patterns in admitted blunt trauma patients with and without prehospital spinal motion restriction - James Vosswinkel; Jonathan Martin; Zhe Wang; Adam J Singer; Emily Huang; Randeep Jawa; Susan Jao; Ambika Mukhi; Neeta Chaudhary; Victoria Yuan; Robert Laskowski (Trauma Surgery & Acute Care Open)
Objectives Selective prehospital cervical spine motion restriction (C-SMR) following blunt trauma has increasingly been used by emergency medical service (EMS) providers. We determined rates of prehospital C-SMR and concomitant radiographic injury patterns.Methods A retrospective trauma registry and chart review was conducted for all adult blunt trauma patients who were transported by EMS and hospitalized with radiographic cervical spine injuries from 2011 to 2019 at a level 1 trauma center.Results Of 658 admitted blunt trauma patients with confirmed cervical spine injury by imaging, 117 (17.8%) did not receive prehospital C-SMR. Patients without prehospital C-SMR were significantly older (76 vs 54 years), more often had low fall as mechanism of injury (59.8% vs 15.9%) and had lower Injury Severity Score (10 vs 17). Patients without C-SMR (Non-SMR) experienced the full array of cervical spine injury types and locations. While the non-SMR patients most often had dens fractures,C-SMR patients most often had C7 fractures; frequencies of fractures at the remaining vertebral levels were comparable. On MRI, cervical spinal cord (8.5% vs 19.6%) and ligamentous injuries (5.1% vs 12.6%) occurred less often in non-SMR patients. Approximately 8.5% of non-SMR patients and 20% of C-SMR patients required cervical spine surgery.Conclusion Patients without prehospital C-SMR demonstrate a broad array of cervical spine injuries. While the rates of certain cervical injuries are lower in prehospital non-SMR patients, they are not insignificant.Level of evidence Level III.